ABCA4 c.6480-35A>G, a novel branchpoint variant associated with Stargardt disease - Rodríguez-Hidalgo, María; de Bruijn, Suzanne E.; Corradi, Zelia; Rodenburg, Kim; Lara-López, Araceli; Valverde-Megías, Alicia; Ávila-Fernández, Almudena; Fernandez-Caballero, Lidia; Del Pozo-Valero, Marta; Corominas, Jordi; Gilissen, Christian; Irigoyen, Cristina; et al. (Frontiers in Genetics, 2023)
Introduction: Inherited retinal dystrophies (IRDs) can be caused by variants in more than 280 genes. The ATP-binding cassette transporter type A4 (ABCA4) gene is one of these genes and has been linked to Stargardt disease type 1 (STGD1), fundus flavimaculatus, cone–rod dystrophy (CRD), and pan-retinal CRD. Approximately 25% of the reported ABCA4 variants affect RNA splicing. In most cases, it is necessary to perform a functional assay to determine the effect of these variants. Methods: Whole genome sequencing (WGS) was performed in one Spanish proband with Stargardt disease. The putative pathogenicity of c.6480-35A>G on splicing was investigated both in silico and in vitro. The in silico approach was based on the deep-learning tool SpliceAI. For the in vitro approach we used a midigene splice assay in HEK293T cells, based on a previously established wild-type midigene (BA29) containing ABCA4 exons 46 to 48. Results: Through the analysis of WGS data, we identified two candidate variants in ABCA4 in one proband: a previously described deletion, c.699_768+342del (p.(Gln234Phefs*5)), and a novel branchpoint variant, c.6480-35A>G. Segregation analysis confirmed that the variants were in trans. For the branchpoint variant, SpliceAI predicted an acceptor gain with a high score (0.47) at position c.6480-47. A midigene splice assay in HEK293T cells revealed the inclusion of the last 47 nucleotides of intron 47 creating a premature stop codon and allowed to categorize the variant as moderately severe. Subsequent analysis revealed the presence of this variant as a second allele besides c.1958G>A p.(Arg653His) in an additional Spanish proband in a large cohort of IRD cases. Conclusion: A splice-altering effect of the branchpoint variant, confirmed by the midigene splice assay, along with the identification of this variant in a second unrelated individual affected with STGD, provides sufficient evidence to classify the variant as likely pathogenic. In addition, this research highlights the importance of studying non-coding regions and performing functional assays to provide a conclusive molecular diagnosis.